Nilai Sosial dalam Novel Dua Garis Biru Karya Lucia Priandarini dan Implikasinya terhadap Pembelajaran Bahasa Indonesia (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The purpose of this research is to identify and analyze the social value of the novel Dua Garis Biru by Lucia Priandarini. The method used in this research is a qualitative descriptive method with data analysis techniques. The results of this study are 82 findings consisting of the value of compassion, the value of helping, religious values, the value of caring, the value of togetherness, the value of responsibility, and the value of forgiveness. Based on the social values ​​in the novel Dua Garis Biru by Lucia Priandarini, there are seven social values, including: the value of affection 23.17%, the value of helping 6.09%, the value of religious 7.31%, the value of caring 34.14%, the value of togetherness 9.75%, the value of responsibility 12.5%, and the value of forgiving each other 7.31%. In these finding, the dominant social value in Lucia Priandarini's novel Dua Garis Biru is the value of caring.